The Eﬀect of the Maqashid Sharia Index, Company Size, and Company Age on Islamic Social Reporting - Vivi Nor Khoiriyah; Kautsar Riza Salman (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
Islamic social reporting is the application of social functions that are based on sharia provisions. It does not only help the Muslims in deciding but also helps companies to fulﬁll their obligations to God and the community. This study aims to obtain empirical evidence on the inﬂuence of maqashid sharia index, company size, and company age on Islamic social reporting and the example is the 11 sharia banks in Indonesia. This study takes about 4 years (2015-2018) and the analysis technique was a descriptive and statistical analysis. Statistical analysis uses the Partial Least Square approach (Smartpls version 3.0) and the result is indicated that the maqashid sharia index, company size, and company age have a positive eﬀect on Islamic social reporting. This study empirically proves that a sharia bank that is able to express the maqashid sharia index well then has good Islamic social reporting disclosure. The sharia banks that have high total assets and income tends to make an extensive Islamic social reporting disclosures because there are also more sources of funds used to make disclosures. The longer sharia bank is established, the higher level of Islamic social reporting disclosure.